Dietary Intake and Fecal Excretion of Titanium Dioxide in U.S. Adults From Lowell, Massachusetts. (7th June 2021) - Putra, Christianto; Bello, Dhimiter; Tucker, Katherine; Kelleher, Shannon; Mangano, Kelsey
Abstract: Objectives: Engineered nanomaterials, such as titanium dioxide (TiO2 /E171) are used in food primarily as a whitening agent. Over 99% ingested TiO2 passes to the gastrointestinal (GI) tract while 1% is absorbed and shown to bioaccumulate in organs and may cause adverse outcomes. At present, dietary exposure of TiO2 in the US is unknown. The objective is to estimate dietary TiO2 and measure TiO2 output in matched stool samples as a biological marker of intake. Methods: Participants ( n  = 51), aged 18–30 y, were recruited in Lowell, MA and were eligible if they had not taken laxatives/antibiotics in the past 6 mo, free of GI disease and no history of GI alterations. Recent dietary intake was assessed by 3, 24-h recalls (NDSR2019) and estimated TiO2 intake is presented as the average of the 3 days. A published database of TiO2 content in foods (Netherlands), with extrapolations for similar US foods, was used to estimate TiO2 exposure. To capture TiO2 excretion, stool samples ( n  = 3) were collected the same day of diet recall. TiO2 was measured in reported foods suspected to contain TiO2 to improve the database. Concentrations of TiO2 in food and stool samples were measured using inductively coupled plasma mass spectrometry following acid digestion. Results: Mean age was 23 ± 3 y; BMI 27 ± 5 kg/m 2 ; 52.9% female. Mean estimated TiO2 intake was 0.13 ± 0.28 mg/kgbw /d (median: 0.03; range: 0.01–1.63 mg/kgbw /d). Mean measured TiO2 concentration in stool samples was 0.107 ± 0.134 mg/mg (median: 0.043; range: 0.005–0.536 ug/mg). Food analysis showed TiO2 content varies widely and is dependent on brand. The top 5 contributors to TiO2 intake in this sample were frostings (62.2%), sauces (8.7%), grains (5.3%), chewing gum (4.43%), and commercial desserts – miscellaneous (3.3%). No association was observed between reported TiO2 intake and measured stool concentration. Conclusions: To our knowledge, this is the first study to assess dietary TiO2 in the US using a validated dietary method and stool excretion. Estimated TiO2 intakes were similar to those in the Netherlands (0.17 mg/kgbw /d), but lower than previous estimates for the US, via Monte Carlo simulation (0.7 mg/kgbw /d). Improvement in the food database is needed to study the effects of chronic TiO2 intake on health outcomes, such as gut health and the microbiome. Funding Sources: None.